Exploring Politeness Strategies Among Fifth-Grade Students: A Sociopragmatic Analysis of Classroom Interactions - Darmawati Darmawati; Mohammad Tahir; Ulinsa Ulinsa (Journal of Innovation and Research in Primary Education, 2026)
This study investigated linguistic politeness among fifth-grade elementary students at SD Alkhairaat Solonsa through a sociopragmatic lens. Despite the importance of polite language in character formation, students often demonstrate inconsistent adherence to politeness norms in school interactions. This qualitative descriptive study employed purposive sampling to examine students' verbal interactions across various school contexts. Data were collected through naturalistic observation, audio recording, and field notes, then analyzed using Miles and Huberman's interactive model with Brown and Levinson's politeness framework. Results revealed two primary utterance forms: polite utterances employing negative and positive politeness strategies that maintain social harmony, and impolite utterances characterized by face-threatening acts lacking mitigation strategies. Polite language served critical functions including relationship maintenance, conflict avoidance, and respect demonstration. Impoliteness emerged from the interplay of internal factors (limited pragmatic competence, immature emotional regulation) and external factors (family communication patterns, peer influence, school culture). Students demonstrated contextual variability, employing polite strategies with teachers while exhibiting impoliteness with peers. Findings extend politeness theory by demonstrating Brown and Levinson's framework applicability to Indonesian elementary contexts, addressing a significant knowledge gap in primary education politeness research. Practically, results suggest fostering linguistic politeness requires integrated pedagogical approaches combining explicit instruction, teacher modeling, and emotional regulation development alongside linguistic repertoire expansion.